The forensic disclosure model: What should be disclosed to, and by, forensic experts? - Almazrouei, Mohammed A. (International journal of law, crime and justice, 2019)
Legal disclosure issues have predominantly focused upon what evidence the prosecution provided or withheld from the defence. In this paper we expand the concept of disclosure to wider contexts in which disclosure failures may result in miscarriages of justice. We introduce a conceptual model of ‘forensic disclosure' which addresses what information should be disclosed to forensic examiners, as well as what information should be disclosed by forensic examiners. This paper presents a holistic overview of the dynamic interactions of four categories of stakeholders: forensic services, investigation, legal, and external stakeholders. We discuss the effective implementation of the forensic disclosure model by addressing five questions: when? What? How? Who? and why? should information be best given to, and by, forensic examiners in order to increase the quality of forensic decision making and to minimise bias.